2020
DOI: 10.3390/molecules25112664
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Cu2+, Zn2+, Ni2+, Fe3+, and Cr3+ Metal Ions Removal from Industrial Wastewaters by Chitosan-Based Composite Cryogels

Abstract: Materials coming from renewable resources have drawn recently an increased attention in various applications as an eco-friendly alternative in the synthesis of novel functional materials. Polysaccharides, with their prominent representative – chitosan (CS), are well-known for their sorption properties, being able to remove metal ions from dilute solutions either by electrostatic interactions or chelation. In this context, we proposed here a comparative study on Cu2+, Zn2+, Ni2+, Fe3+, and Cr3+ metal ions remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
0
14
1
Order By: Relevance
“…Composite gels based on polyelectrolytes represent a class of composite soft materials consisting of hydrophilic charged/uncharged chains that absorb a high content of water (>95%) [133]. These low cost and high efficient 3D-dimensional networks are based on polyelectrolytes of different types: (i) synthetic, such as: PEI [36,92], PAH [93,118], PAA [38], PAMPS [106,118,119], or (ii) natural, like the following: CS [30,[32][33][34]38,39], modified CS [37,84,85], SA [33,70,73], modified SA [72], modified cellulose [104]. Many studies reported the incorporation of organic/inorganic entities into the gel structure, including GO [70,73], Fe 3 O 4 [36,106], SiO 2 [113], zeolites [30,32], clays [72].…”
Section: Composite Gels (Hydrogels Monolith Cryogels Sponges)mentioning
confidence: 99%
“…Composite gels based on polyelectrolytes represent a class of composite soft materials consisting of hydrophilic charged/uncharged chains that absorb a high content of water (>95%) [133]. These low cost and high efficient 3D-dimensional networks are based on polyelectrolytes of different types: (i) synthetic, such as: PEI [36,92], PAH [93,118], PAA [38], PAMPS [106,118,119], or (ii) natural, like the following: CS [30,[32][33][34]38,39], modified CS [37,84,85], SA [33,70,73], modified SA [72], modified cellulose [104]. Many studies reported the incorporation of organic/inorganic entities into the gel structure, including GO [70,73], Fe 3 O 4 [36,106], SiO 2 [113], zeolites [30,32], clays [72].…”
Section: Composite Gels (Hydrogels Monolith Cryogels Sponges)mentioning
confidence: 99%
“…The overall porosity of the CS cryogels (P, %) was estimated by the liquid displacement technique, and was calculated by Eq. (2) [4,6].…”
Section: Structural and Morphological Characterizationmentioning
confidence: 99%
“…Compared to conventional adsorbents such as activated carbon (AC) or synthetic ion exchangers, biopolymers represent valuable alternatives for sorption of various contaminants [1][2][3]. Consequently, over the years numerous biopolymers have been used as main matrix to develop composite-based sorbents for removal of heavy metal ions (HMIs) [4][5][6], dyes [7,8], or other pollutants [9,10]. One of the most promising biopolymers is chitosan (CS), a low-cost renewable polycation which is obtained from shells of crustaceans (crabs, shrimps, lobsters, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the discharge of HMIs from aqueous solutions has been intensively carried out using various processes, including chemical precipitation, extraction with different solvents, flocculation, ion exchange, ultrafiltration, reverse osmosis and adsorption [5][6][7][8][9][10]. Among these, adsorption is considered a simple and efficient technique to remove HMIs from wastewaters [8][9][10][11][12]. A large variety of sorbent materials, such as metal oxides/hydroxides [13,14], zeolites [15,16], commercial or synthetic activated carbon [17,18], biomass [19], synthetic organic supports [6,8,9], and unmodified or functionalized polysaccharides (chitosan, salecan, pullulan, alginate) [20][21][22][23][24][25][26][27][28][29] have been reported to remove HMIs from contaminated waters.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the employment of inexpensive and eco-friendly sorbents, such as renewable natural polymers, in the extraction and recovery of certain HMIs has drawn considerable interest [2,3,10,11,[20][21][22][23][24][25][26][27][28][29]. Amongst these low-cost sorbents, chitosan (CS) displayed promising abilities to bind different HMIs due to the presence of numerous amino and hydroxyl groups in its structure [2,20,27].…”
Section: Introductionmentioning
confidence: 99%